Pengaruh Kemajuan Teknologi Informasi Terhadap Perkembangan Akuntansi - Arya Thresna H.S,; Muhamad Machfudi,; Charisma Yoan Nurotul Azizah,; Farah Azzahra Dini,; A. Nurul Khaeria, (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
The rapid advancement of Information Technology has resulted in significant changes to the world of accounting, both in terms of human resources and the supporting tools of an accountant. The development of accounting is a technological advancement that takes place in three stages, namely the agricultural era, the industrial era, and the information age. The role of information technology in the development of accounting at each different stage. Information technology affects the information system of increasingly advanced accounting advances, as can be seen from improvements in data processing, internal control, increased productivity, efficiency, and quality of information in financial reporting. The development of computer-based AIS in the preparation of financial statements also affects the audit process. Then, advances in information technology also present new opportunities for the accounting profession. New opportunities that may become a reality are Computer Information Systems Consulting, CISA, and Web Trust Audits.